Toxina botulínica para uso terapéutico - Fernandez, Rafael Alfredo (2006)
From the year 1980 the intramuscular inoculation of botulinal neurotoxin (BoNT) is realized for treatment of disorders of the muscular tone. The simplicity of the treatment does an excellent alternative to the surgery. The p rincipal action is a flaccid muscular palsy that needs between 2 and 6 months for its rec overy. As for the therapeutic rank, the BoNT would overcome in safety to the majority o f the drugs. In the latter decade the use of the therapy with BoNT has experimented an am azing growth, with new and mul- tiple indications, especially neurological, and has turned into the treatment of aesthetic medicine with more rapid growth into his demand. It would be ideal to obtain prepara- tions that: during the making and storage the toxic ity does not diminish significantly, could be stored to ambient temperature, support maj or time the activity and with dimin- ished capacity of diffusion and of formation of ant ibodies. The effect is not instantane- ous, but progressive in the first days and ideally between 1 and 2 weeks later. Between 3 and 4 months later, the effect starts diminishing and the muscles contract again. The result is not the definitive remedy, and repeated d oses being needed. Its use is limited by economic reasons.